Essentials of Autopsy Practice Updates and Reviews to Aid Practice - Rutty, Guy N.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2022)
This book covers topical subjects within the field of death investigation, where changes in practice have recently occurred. The topics embrace the multi-disciplinary approach required for death investigation, and address advances in the fields of forensic fractography in relation to road traffic death investigations, pathology, MicroCt and 3D printing as applied to forensics. Chapters are written in a uniform easy-to-follow format to ensure they are accessible to both specialists and non-specialists in the field. Essentials of Autopsy Practice $1 (BUpdates and Reviews to Aid Practice is a practical resource covering the latest advances in autopsy practice, making it an ideal resource for trainees, consultants, generalists and specialists, along with multi-disciplinary teams working in this field.s
Forensic application of (3z(BFree-D(3y (Bsoftware -- Post-mortem cardiac magnetic resonance imaging -- The use of micro-computed tomography for forensic applications -- The role of fractography in forensic pathology and forensic anthropology examinations -- The application of radiographic imaging in forensic odontology -- Disaster victim identification: Traditional approaches and changing practices -- Examining an already autopsied or exhumed body -- Death associated with trees -- Mountain death revisited: Mass slope movements, mountain associated suspension and volcanos.s
Keywords: Pathology; Internal medicine; Radiology; Pathology; Internal Medicine; Radiology; Autopsy; Forensic Medicine; Pathology